VALID GARNET-BIOTITE (GB) GEOTHERMOMETRY AND GARNET-ALUMINUM SILICATE-PLAGIOCLASE-QUARTZ (GASP) GEOBAROMETRY IN METAPELITIC ROCKS - Wu C.M.; Cheng B.H. (My University, 2006)
At present there are many calibrations of both the garnet-biotite (GB) thermometer and the garnet-aluminum silicate-plagioclase-quartz (GASP) barometer that may confuse geologists in choosing a reliable thermometer and/or barometer. To test the accuracy of the GB thermometers we have applied the various GB thermometers to reproduce the experimental data and data from natural metapelitic rocks of various prograde sequences, inverted metamorphic zones and thermal contact aureoles. We have concluded that the four GB thermometers (Perchuk, L.L., Lavrent'eva, I.V., 1983. Experimental investigation of exchange equilibria in the system cordierite-garnet-biotite. In: Saxena, S.K. (ed.) Kinetics and equilibrium in mineral reactions. Springer-Verlag New York, Berlin, Heidelberg. pp. 199-239.; Kleemann, U., Reinhardt, J., 1994. Garnet-biotite thermometry revised: the effect of AlVI and Ti in biotite. European Journal of Mineralogy 6, 925-941.; Holdaway, M.J., 2000. Application of new experimental and garnet Margules data to the garnet-biotite geothermometer. American Mineralogist 85, 881-892., Model 6AV; Kaneko, Y., Miyano, T., 2004. Recalibration of mutually consistent garnet-biotite and garnet-cordierite geothermometers. Lithos 73, 255-269. Model B) are the most valid and reliable of this kind of thermometer. More specifically, we prefer the Holdaway (Holdaway, M.J., 2000. Application of new experimental and garnet Margules data to the garnet-biotite geothermometer. American Mineralogist 85, 881-892.) and the Kleemann and Reinhardt (Kleemann, U., Reinhardt, J., 1994. Garnet-biotite thermometry revised: the effect of AlVI and Ti in biotite. European Journal of Mineralogy 6, 925-941.) calibrations due to their small errors in reproducing the experimental temperatures and good accuracy in successfully discerning the systematic temperature changes of the different sequences. In addition, after applying the GASP barometer to 335 natural metapelitic samples containing one kind of aluminosilicate and 33 natural metapelitic samples containing two kinds of aluminosilicate, as well as to rocks in limited geographic areas and thermal contact aureoles, we propose that the calibrations of Holdaway (Holdaway, M.J., 2001. Recalibration of the GASP geobarometer in light of recent garnet and plagioclase activity models and versions of the garnet-biotite geothermometer. American Mineralogist 86, 1117-1129.) and Newton and Haselton (Newton, R.C., Haselton, H.T., 1981. Thermodynamics of the garnet-plagioclase-Al2SiO5-quartz geobarometer. In: Newton, R.C., Navrotsky, A., Wood, B.J. (eds.) Thermodynamics of minerals and melts. New York: Springer-Verlag. 131-147.); based on Kleemann and Reinhardt's (Kleemann, U., Reinhardt, J., 1994. Garnet-biotite thermometry revised: the effect of AlVI and Ti in biotite. European Journal of Mineralogy 6, 925-941.) thermometer) are the most valid GASP barometers. Other GB thermometers and GASP barometers are not recommended. © 2005 Elsevier B.V. All rights reserved.
Keywords: ALUMINOSILICATE; GEOBAROMETRY; GEOTHERMOMETRY; METAPELITE